A 4 DOF simulation model developed for fuel consumption prediction of ships at sea. (3rd October 2019) - Tillig, Fabian; Ringsberg, Jonas W.
ABSTRACT: The study presents a new simulation model for the prediction of the fuel consumption of ships at sea. The model includes external forces and moments caused by the environment at sea, i.e. wind, waves and ocean currents, and solves the force and moment balances for the ship with four degrees-of-freedom (4 DOF), i.e. surge, drift, yaw and heel. To capture involuntary speed losses, engine limits are included in the model. By combining an existing power prediction model, a numerical standard hull and propeller series, and numerous empirical methods, the simulation model can be applied to conventional ships with very limited information available at the outset of an analysis, e.g. the main dimensions, engine rpm and propeller rpm. Additionally, a wind-assisted propulsion component is available. The current study describes the details of the 4 DOF model together with its applicability on three case studies on a ship route through the Baltic Sea with realistic weather forecasts. The main conclusions of the study show that there are considerable differences in the predicted fuel consumption when comparing simulation results based on 1 DOF and 4 DOF; the 4 DOF simulation model is recommended. It is shown that it is crucial to include the yaw moment balance and limits for the rudder angle when analysing ships with wind-assisted propulsion. Examples of involuntary speed losses and different modes of operation are compared and discussed, and potential problems with propeller backside cavitation and engine stalling when running a ship with a wind-assisted device are discussed.